Earth(q)wake introducing preemptive seismic urbanism model in seismic planning as applied to the context of Metropolitan Manila - Buenaventura, Vera M.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
In recent years, the talk of the 'Big One' has been brought up as a threat to paralyze Metropolitan Manila which prompted continuous research in the field of physical science and active conduction of drill programs. Despite these efforts, less forecasted implications, such as evacuation of its people, individual and communal sufficiency, and immediateness of response, are more difficult to prepare for. Through introduction of a landscape process-specific to earthquake planning, an urban concept and model are theorized to understand and integrate systems of urban hierarchy and communal context-sensitivity as equally relevant and vital for future urban development, emergency planning, and risk-reduction. In summary, the Preemptive Seismic Urbanism model with the introduction of the urban unit concept takes on the linear process of planing encompassing regional scale for an inclusive point of view in seismic context, down to urban unit scale to inhibit a context-sensitive plan. The theoretical foundation of the concept and model considers the Filipino culture of disaster as an asset in evolving coping mechanism that matches the structure of the society. This include emergency protocol and frameworks which are augmented to establish a system that is suitable in the capacity of the urban condition as well as the capability of the people as part of the emergency mechanism. It also employs targeted planning action which solutions are oriented to blending in the simple and appropriate measures of public environment recovery and security to veer away from technological dependency and to make feasible implementatio of scheme.
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Seismic planning; Preemptive Seismic Urbanism model